Iriye, Japan And The Wider World - From The Mid-Nineteenth Century To The Present - Wyatt, Lee (Teaching History: A Journal of Methods, 1998)
Iriye’s book is an expansion of two earlier works by this leading Japanese American scholar previously published in Japan in the 1960s and early 1990s. It is an extremely readable survey of Japan’s history and place in the world between the mid-nineteenth and end of the twentieth centuries. Beginning with the Meiji Restoration of 1868 and ending with the post-Cold War world, Iriye provides not only an historical account of the Japanese effort to move from isolation to a significant role in the modem world but, more importantly, an emphasis on how the Japanese viewed themselves during this period in the context of the nation, Pacific Basin, world, and even internal dynamics.